Essentials of biology - Mader, Sylvia S.; Windelspecht, Michael 1963- (McGraw-Hill, 2024)
"Essentials of Biology, seventh edition is designed to provide students who are not majoring in science with a fundamental understanding of the science of biology. Even though these students are not scientists, an understanding of how science can help identify, analyze, and offer solutions to the many challenges facing human society is critical to our species' health and survival"--Provided by publisher.